Fragment of the aspartyl-tRNA synthetase applicable as a shared classification and phylogenetic marker in particular representatives of the order Lactobacillales - Mekadim, Chahrazed; Killer, Jiří; Pechar, Radko; Mrázek, Jakub (Folia microbiologica, 2019)
The order Lactobacillales represents a morphologically, metabolically, and physiologically diverse group of bacteria. Lactic acid bacteria represent the core of this phylogenetic group. They are a part of epiphytic microflora, fermented dairy, meat, fruit and vegetable products, and the digestive tract of humans and animals. Despite the fact that these bacteria form a phenotypically and genotypically heterogeneous group, their phylogenetic relationship enables to propose a common genetic marker usable in classification, typing, and phylogeny. By creation of consensus sequence based on available genomic sequences of some representatives of order Lactobacillales, a specific primer-pair binding variable region of aspS gene (length of 615 nts) encoding the aspartyl-tRNA synthetase was designed. This gene has not yet been used in classification and phylogeny of the order Lactobacillales, although it meets the requirements of molecular markers (distribution and single copy in bacterial genomes, functional constancy and genetic stability, sequence variability among taxonomic units, irreplaceable role in proteosynthesis). Primers were applied on 54 type and wild Lactobacillales strains. Obtained sequences allowed to provide alignments for purpose of phylogenetic tree reconstructions that uncovered particular phylogenetic clusters of vagococci/enterococci, obligately homofermentative and heterofermentative lactobacilli. Although a relatively short fragment of the aspS gene (approximately 33% of the complete gene sequence) was evaluated, much higher sequence variability (61.8% of pairwise identity) among strains examined compared with 16S rRNA gene (90.7%, length of 1318 nt) provides a relatively simple and effective tool for classification and typing of selected representatives of the order Lactobacillales.
Keywords: bakteriální proteiny; Phylogeny; DNA, Bacterial; Genetic Markers; RNA, Ribosomal, 16S; Sequence Analysis, DNA; esenciální geny; RNA ribozomální 16S; Lactobacillales; DNA bakterií; Bacterial Proteins; Aspartate-tRNA Ligase; Genes, Bacterial; sekvenční analýza DNA; bakteriální geny; aspartát-tRNA-ligasa; genetické markery; fylogeneze; Genes, Essential